HNO-ärztliche Diagnostik und Therapie von Schwindelsyndromen: Referate - Walther, Leif Erik (HNO, 2025)
Vertigo and dizziness are common key symptoms in clinical practice and can significantly impair quality of life. Potential consequences include inability to work, reduced social contacts, falls, and secondary illnesses. Otorhinolaryngologists encounter both acute and chronic dizziness syndromes in emergency settings, during interdisciplinary diagnostic testing, and in ENT expert assessments. A structured medical history, targeted communication techniques, and an orienteering initial examination facilitate differential diagnostic classification. In addition, instrumental, objective diagnostics (“mapping” all five vestibular sensors on both sides) provide quantitative insights into the function of vestibular sensors and reflexes. Although diagnostic criteria and evidence-based treatments exist for certain conditions, the overall data situation remains inadequate for many diseases.